The clinical profile of tuberous sclerosis complex (TSC) in the United Kingdom: A retrospective cohort study in the Clinical Practice Research Datalink (CPRD). (March 2016) - Kingswood, Christopher; Bolton, Patrick; Crawford, Pamela; Harland, Christopher; Johnson, Simon R.; Sampson, Julian R.; Shepherd, Charles; Spink, Jayne; Demuth, Dirk; Lucchese, Lara; Nasuti, Paola; Gray, Elizabeth; et al.
Abstract: Background: Tuberous Sclerosis Complex (TSC) is a multi-system genetic disorder characterised by the development of benign growths and diverse clinical manifestations, varying in severity, age at onset and with high clinical burden. Aims: This longitudinal study aims to describe the broad spectrum of clinical manifestation profiles in a large, representative cohort of TSC patients in the UK in order to better understand disease complexity. Methods: TSC patients in the Clinical Practice Research Datalink (CPRD) and linked Hospital Episodes Statistics (CPRD-HES) were retrospectively identified between 1987 and 2013. Available history was extracted for each patient and clinical diagnosis, procedure and medication records reviewed. A random selection of patients from the CPRD-HES was used as a Comparator cohort. Results: Three hundred and thirty-four TSC patients with a mean (SD) age of 30.3 (18.6) years were identified (53% female). TSC was diagnosed at mean age 3.2 (4.2) years. Epilepsy and psychiatric manifestations were reported frequently in paediatric (77% and 55%, respectively) and adult patients (66% and 68%, respectively). The prevalence of manifestations in the TSC cohort was markedly higher versus the Comparator cohort. The majority of paediatric (46%) and adult TSC patients (62%) developed clinical manifestations affecting at least three organ systems and forty-nine distinctive organ system manifestation profiles were identified. Conclusions: TSC patients present with multiple and complex clinical manifestations and profiles that necessitate the co-ordinated action of a multidisciplinary team in order to improve the quality and efficiency of care. Highlights: A retrospective study of 334 TSC patients in the community setting in the UK. TSC patients present with numerous, highly variable clinical manifestation profiles. An inventory of TSC clinical codes by organ system was developed (MedITOSC). Broad spectrum of TSC manifestations, including some infrequently reported. A coordinated MDT approach may improve the quality and efficiency of care in TSC.